Reaganomics: A Historical Watershed - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2018)
The socio-economic impact of Reaganomics and its long-run deleterious legacy is documented. The preponderance of data indicate that economic growth was not particularly impressive in the wake of the tax cuts of 1981 or 1986. GDP did snap back to potential but failed to accelerate beyond the rates achieved in prior or subsequent decades. The supposed incentives of supply-side economics failed to materialize. People did not work more, they did not save or invest more than they did before, and the benefits trickled down like molasses and got stuck at the very top of the income distribution. Instead, Reagan's presidency was a watershed in U.S. economic development in the sense that it reversed many of the accomplishments of the New Deal and inaugurated an era in which low-skilled men's wages began a long period of decline, and labor's share of GDP continued to fall. Reagan's true legacy is a dual economy that accompanied the hollowing out of the middle class, a more business-friendly regulatory and oversight framework for Wall Street that ultimately led to the financial crisis, a stupendous increase in the national debt from 30% to 50% of GDP that put it on a path such that by 2012 it exceeded 100%, anti-statism that contributed to the rise of Trumpism, a remarkable rise in inequality that gave rise to an oligarchy, and the benign neglect of blue-collar workers who eventually became Hillary Clinton's “deplorables.” Reagan put the economy on a trajectory to ultimately, even if not inevitably, led to the triumph of Trumpism and an economy of malaise.
Keywords: B52; D69; H29; H69; N12; P16; 330; reaganomics; Trumpism; tax cuts; supply-side economics; trickle-down economics